Determining University Students' Attitudes Towards Sexual Health: The Case of Nursing Students - KARAKURT, Papatya; KÖSE TUNCER, Sevinç (GEVHER NESIBE JOURNAL OF MEDICAL AND HEALTH SCIENCES, 2022)
Sexual health is a combination of the physical, emotional, intellectual and social aspects of sexuality that enhance personality, communication and love. This study was conducted to determine the attitudes of nursing students towards reproductive health and sexual health. The population of this descriptive study consisted of a total of 459 students studying in the Nursing Department of the Faculty of Health Sciences of a university in the academic year of 2021-2022. Sample selection was not made from the population and the study was completed with 340 students who could be reached. In the data collection, the "Information Form" and the "Scale of Attitudes of Nursing and Midwifery Students towards Sexual Health" to determine the attitudes of the students towards sexual health were used. Numbers, percentages, mean, standard deviation, Mann Whitney U test and Kruskal Wallis Analysis were used in the data analysis. It was found that 66.2% of the students did not receive any training on sexual health, 91.8% of the students accessed information about sexual health through the internet, 41.8% from friends and 40.6% from healthcare personnel. There was a statistically significant difference between the students' mean scores of attitudes towards sexual health scale according to the place where they spent most of their lives. The students' mean score of attitudes towards sexual health scale was 46.28±8.60. In this study, it was determined that more than half of the students did not receive training on sexual health, almost all of them accessed information about sexual health via the Internet, and their attitudes towards sexual health were above the medium level.